Analyses of the costs associated with very high turbine entry temperatures in helium recuperated gas turbine cycles for Generation IV nuclear power plants - Gad-Briggs, Arnold; Pilidis, Pericles; Nikolaidis, Theoklis (ASME, 2018)
Previous analyses of Generation IV (GEN IV) helium gas turbine cycles indicated the possibility for high Turbine Entry Temperatures (TETs) up to 1200°C in order to improve cycle efficiency, using improved turbine blade material and optimum turbine cooling fractions. The purpose of this paper is to understand the effect on the Levelised Unit Electricity Cost (LUEC) of the Nuclear Power Plant (NPP), when the TET is increased to 1200°C from an original TET of 950°C and when an improved turbine blade material is used to reduced the turbine cooling fraction. The analyses focus on the Simple Cycle Recuperated (SCR) and the Intercooled Cycle Recuperated (ICR). The baseline LUECs of the NPPs were calculated as $61.84/MWh (SCR) and $62.16/MWh for a TET of 950°C. The effect of changing the turbine blades improved the allowable blade metal temperature by 15% with a reduction in the LUEC by 0.6% (SCR) and 0.7% (ICR). Furthermore, increasing the TET to 1200°C has a significant effect on the power output but more importantly it reduces the LUECs by 22.7% (SCR) and 19.8% (ICR). The analyses intends to aid development of the SCR and ICR including improving the decision making process on choice of cycles applicable to the Gas-cooled Fast Reactors (GFRs) and Very High-Temperature Reactors (VHTRs), where helium is the coolant.
Keywords: Temperature; Gas turbines; Turbines; Cycles; Helium; Nuclear power stations; Turbine blades; Cooling; Metals; Coolants